Representation of illusory and physical rotations in human MST: A cortical site for the pinna illusion. Issue 6 (4th March 2016) - Pan, Yanxia; Wang, Lijia; Wang, Zhiwei; Xu, Chan; Yu, Wenwen; Spillmann, Lothar; Gu, Yong; Wang, Zheng; Wang, Wei
Abstract: Visual illusions have fascinated mankind since antiquity, as they provide a unique window to explore the constructive nature of human perception. The Pinna illusion is a striking example of rotation perception in the absence of real physical motion. Upon approaching or receding from the Pinna‐Brelstaff figure, the observer experiences vivid illusory counter rotation of the two rings in the figure. Although this phenomenon is well known as an example of integration from local cues to a global percept, the visual areas mediating the illusory rotary perception in the human brain have not yet been identified. In the current study we investigated which cortical area in the human brain initially mediates the Pinna illusion, using psychophysical tests and functional magnetic resonance imaging (fMRI) of visual cortices V1, V2, V3, V3A, V4, and hMT+ of the dorsal and ventral visual pathways. We found that both the Pinna‐Brelstaff figure (illusory rotation) and a matched physical rotation control stimulus predominantly activated subarea MST in hMT+ with a similar response intensity. Our results thus provide neural evidence showing that illusory rotation is initiated in human MST rather than MT as if it were physical rotary motion. The findings imply that illusory rotation in the Pinna illusion is mediated by rotation‐sensitive neurons that normally encode physical rotation in human MST, both of which may rely on a cascade of similar integrative processes from earlier visual areas. Hum Brain Mapp 37:2097–2113, 2016 . ©2016 Wiley Periodicals, Inc.